(untitled) (Research, Society and Development, 2023)
According to the World Health Organization, cardiovascular diseases are the leading cause of death in the world. Atherosclerosis is a progressive disease, which is characterized by the accumulation of lipids inside the macrophages, generating an accumulation of fat in the cells that revert to the arteries, in the long run, it may end up leading to the obstruction of these arteries, obstructing the passage of blood to the heart. The present article has as its general objective to expose the antioxidant activity present in food, thus evidencing its beneficial effects in the prevention and control of atherosclerotic disease. It is an integrative literature review. To search and select the studies, the following databases were used: Science Direct, Pudmed and Cochrane, totaling 10 articles, which were published between the years 2015 to 2021. This study is relevant because it serves as a basis for academics, in order to deepen the knowledge in this area that will always be in increasing evidence, in addition to stimulating other studies of this nature.